Student Management System (SMS) for kolej komuniti in Mesiniaga - Kitikan, Andarian (2009)
The aim of this project is to develop a web based Student Management System (SMS) for Kolej Komuniti attachment program in Mesiniaga Bhd. This system will help Mesiniaga to administer student's related information in efficient manner. Among the main functionality of the system are managing records such as student details, subject list and semester schedule. It also enables the student to view necessary information such as subject list and online result. Software engineering methodology has been applied for entire development of the system. This includes adopting Waterfall Model as a software process and using Object Oriented Analysis and Design (OOAD) as a software technique. Both system requirements specification and system design have been carefully studied and documented using guidelines from Department of Defense (DoD), specifically, MIL-498. Ultimately, the system has been implemented using sophisticated Java web framework namely Apache Struts 2 with other emerging technology such as Apache Tiles 2, Java Persistence API (JPA) and Hibernate.